2020
DOI: 10.1063/5.0002044
|View full text |Cite
|
Sign up to set email alerts
|

Capture of rod-like molecules by a nanopore: Defining an “orientational capture radius”

Abstract: Both the translational diffusion coefficient D and the electrophoretic mobility µ of a short rod-like molecule (such as dsDNA) that is being pulled towards a nanopore by an electric field should depend on its orientation. Since a charged rod-like molecule tends to orient in the presence of an inhomogeneous electric field, D and µ will change as the molecule approaches the nanopore, and this will impact the capture process. We present a simplified study of this problem using theoretical arguments and Langevin D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 42 publications
(52 reference statements)
8
36
0
Order By: Relevance
“…They recovered the orientational capture radius we defined previously and concluded that rods do not follow field lines during capture due to the anisotropic diffusion. 12 Furthermore, they showed that the trajectory of a rod towards the nanopore depends on its initial orientation and position because of the near-wall hydrodynamic interactions (these interactions were missing in our previous work). However, the electrostatic interactions between the rod and the ions in solution are still missing in their calculation; such interactions can change the dynamics, for instance when the rod is in the high field region near (or inside) the nanopore or when the rod is not uniformly charged.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…They recovered the orientational capture radius we defined previously and concluded that rods do not follow field lines during capture due to the anisotropic diffusion. 12 Furthermore, they showed that the trajectory of a rod towards the nanopore depends on its initial orientation and position because of the near-wall hydrodynamic interactions (these interactions were missing in our previous work). However, the electrostatic interactions between the rod and the ions in solution are still missing in their calculation; such interactions can change the dynamics, for instance when the rod is in the high field region near (or inside) the nanopore or when the rod is not uniformly charged.…”
Section: Introductionmentioning
confidence: 88%
“…For our purposes here, we define the electrophoretic mobility as the constant linking the mean magnitude of the instantaneous velocity and the magnitude of the applied field:〈| v e |〉 = μ e | E |.Taking the norm (|…|) is not necessary when the velocity and the force point in the same direction, but this is not always the case for rods when EHI effects are included, as we shall see. Similarly, we define the friction coefficient in the presence of the external mechanical force using the expression| F m | = γ m 〈| v m |〉.To characterize rod orientation, we use the order parameter 12 where θ is the angle between the direction of the force and the rod's principal axis.…”
Section: Free Solution Electrophoresismentioning
confidence: 99%
See 1 more Smart Citation
“…After retrieving I/V information, translocation experiments with λ -DNA at 500 pM were performed. When EPF dominates, the capture volume outside the nanopore assumes a nearly spherical shape surrounding the pore's oriface [26][27][28][29][30] . As ionic strength decreases, EOF can dominate as the primary means for DNA entering the pore.…”
Section: Resultsmentioning
confidence: 99%
“…Typically in experimental salt concentrations a dsDNA has a screened partial charge of 0.2-0.3 times the charge of an electron. 34 With the electric eld present beyond the pore, it will be worthwhile to study how the addition of a screened coulomb charge on the DNA monomer 35,36 in our model will affect the ossing. We believe our results will promote new experimental and theoretical studies on nanopore translocation.…”
Section: Summary and Future Workmentioning
confidence: 99%